Studi Empiris Pengaruh Persepsi Kemudahan dan Manfaat terhadap Keputusan Menggunakan QRIS di Tangerang - Adji, Muhammad Azrival Sentanu; Sukmawati, Kartika (Soratekno Publisher, 2025)
This study aims to analyze the influence of perceived ease of use and perceived usefulness on the decision to use Quick Response Code Indonesian Standard (QRIS) in the Tangerang area. The research employs a quantitative method with a primary data approach, collected through the distribution of questionnaires to 100 respondents who have used QRIS. The sampling technique used is non-probability sampling with a purposive sampling approach. Data analysis includes validity testing, reliability testing, multicollinearity testing, heteroscedasticity testing, normality testing, multiple linear regression analysis, F-test (simultaneous), t-test (partial), and the coefficient of determination (R²). The results of the analysis show that perceived ease of use and perceived usefulness simultaneously have a significant influence on the decision to use QRIS. However, partially, only perceived usefulness has a significant effect on the decision to use QRIS, while perceived ease of use does not show a significant influence. These findings indicate that although ease of use is important, the usefulness perceived by users is the key factor in driving the decision to use QRIS in Tangerang.